The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1109/60.911396
|View full text |Cite
|
Sign up to set email alerts
|

Optimum siting of wind turbine generators

Abstract: This paper investigates optimum siting of wind turbine generators from the viewpoint of site and wind turbine generator selection. The methodology of analysis is based on the accurate assessment of wind power potential of various sites. The analytical computations of annual and monthly capacity factors are done using the Weibull statistical model using cubic mean cube root of wind speeds. As many as fifty-four potential wind sites, with and without wind turbine installations, geographically distributed in diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(48 citation statements)
references
References 4 publications
(1 reference statement)
0
45
0
Order By: Relevance
“…This estimation of the CDFs can be done parametrically or non-parametrically. In this paper for brevity, we shall follow the nonparametric approach on the NREL data, mindful that as in [29] we could have employed a given parametric CDF (with its parameters obtained either through sample fitting or from a transformation of a Weibull distribution through the turbine curve; see for instance [37]) with similar results.…”
Section: Mixed Formulation Of the Wind Power Distributionmentioning
confidence: 99%
“…This estimation of the CDFs can be done parametrically or non-parametrically. In this paper for brevity, we shall follow the nonparametric approach on the NREL data, mindful that as in [29] we could have employed a given parametric CDF (with its parameters obtained either through sample fitting or from a transformation of a Weibull distribution through the turbine curve; see for instance [37]) with similar results.…”
Section: Mixed Formulation Of the Wind Power Distributionmentioning
confidence: 99%
“…The mono-objective function to be maximized is the total instantaneous mechanical power conversion (see Sections 3.1.1 and 3.1.2 for details) of the wind farm (defined as the sum of the power conversion of all the WTs, which can be determined using Equation (2)), while considering wake effects (e.g., the Jensen-Katic wake model, Equations (15) and (39), and the wake superposition by sum of squares of velocity deficits method, Equation (41), are assumed). The design variables ( ∈ {0,1}, ∀ ∈ {1,2, … , } ) represent if a WT is located or not on each discretized space.…”
Section: The Computational Complexity Of the Wfdo Problemmentioning
confidence: 99%
“…Based on this coarse wake-interaction modeling, it was concluded that quite large separations between WTs were required to avoid significant wake-based energy losses. In the subsequent years, staggered equally-spaced (or grid-like) siting schemes were slowly adopted as a rule-of-thumb by wind farm designers [11][12][13][14][15][16][17]. In the late 1970s and the early 1980s, just after the construction of the world's first electricity-generating wind farm in New Hampshire (USA) in 1980, the first engineering wake models [18][19][20][21][22][23][24], mostly based on flow momentum conservation and linearized far wake expansion assumptions (with the notable exception of the Larsen [25] and Ainslie [26] models), appeared, laying the groundwork for the first study on Wind Farm Design and Optimization (WFDO) [27], which aimed at optimizing the spacing between WTs in a linear array by using a generalized reduced gradient method that maximized the total power conversion of the array.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a variety of PDFs have been proposed in literature to describe wind , are also applied to wind energy analysis recently, and they have been proved to be more effective than unimodal types for wind regimes with bimodal distribution. A number of detailed reviews on modeling the probability distributions of wind speed in wind energy analysis can be found in references [20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%